Dietary effect of mushroom (Agaricus bisporus) powder on growth performance of commercial broiler (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The study was performed for investigating the dietary effect of different levels of mushroom (Agaricus bisporus) powder on the performance of broiler. Four experimental rations designated as T0, T1, T2 and T3 having 0g, 5g, 8g and 10g dried mushroom powder/kg of feed was fed to 120 broiler chicks (Cobb 500), randomly distributed into 8 replicates, so as to have 2 replicates per treatment containing 15 chicks in each. The experiment was carried out for 30 days. Average weight gain, feed consumption, feed efficiency, dressing yield and survivability were used as criteria of response to feeding mushroom powder. Organs weight including heart, liver and gizzard were also recorded. The mean body weight per broiler was 1292.24, 1501.66, 1445.19 and 1434.97g in 30 days for the treatment of groups T0, T1, T2, and T3 respectively (P